AMBIGUITY OF LOCI DURING HLA-TYPING ON SSO TECHNOLOGY AND ATTEMPT TO RESOLVE THEM - M. A. Loginova (Vestnik Transplantologii i Iskusstvennyh Organov, 2010)
Sequence specific oligonucleotides typing was used to identify human leukocyte antigen (HLA)-A, B, DRB1 alleles from 705 recruited volunteers with Volga Federal District for unrelated hematopoietic stem cell registry and 155 of their number at locus HLA-C. 48 samples cannot be entered into the database because of ambiguities in the identification of allelic loci on HLA-class I – HLA-A, HLA-B. To resolution of ambiguity use reagents kits AlleleSEQR HLA Sequencing, which allowed to reveal the ambiguity of the locus HLA-A, 44% of cases, the loci HLA-B and HLA-C – 40% of cases. Application software HARPs Finder showed the possibility of resolution of all identified allelic ambiguities (with the exception of types of ambiguity – A*03/A*32 or A*74:13/A*32:04 and A*01/A*11 or A*36:04/A*11) with the addition of basic kits AlleleSEQR HLA Sequencing reagents kit Al- leleSEQR HARPs.